Pour une approche socio-écosystémique de la dette écologique : une responsabilité civile spécifique en cas d’atteintes à l’environnement - Marie-Pierre Camproux Duffrène (VertigO)
The increase of the pressures on environment induces the question of their reparation. Lawyers can take part in this reflection by proposing adequate legal instruments. The civil liability provides the obligation to persons who caused a damage to repair it. This may represents a useful legal mechanism to stop the threats and repair the ecological damages. However, the fact that environmental damages or the threats thereof do not relate to persons or goods (suitable things) but to elements of an ecosystem, raises some difficulties. This situation implies a reflection on the adaptability of the above mechanism in this field and its capacity to provide access to justice. Fundamentally, does one have to preach an individual right to environment, rights (laws) for the environment or to consider a protection of the collective interests dependent on an environment perceived as a socio-ecosystem ? Otherwise, the civil liability being already actuated in the case of environmental threats, somes specificities are being studied : which legal relationship exists between society and natural environment, or regarding humans versus the environment ? and, especially, in front of a judge, who has the legal standing and in order to claim what ?